A study of the influence of WC-10Co-4Cr HVOF coating on mechanical properties of AISI 4340 steel - Souza, Renato Chaves; Nascimento, Marcelino Pereira Do [UNESP]; Voorwald, Herman Jacobus Cornelis [UNESP]; Pigatin, Walter Luís (SAE International, 2001)
Aircraft landing gear manufacturers are considering WC thermal spray coatings applied by the high-velocity oxygen-fuel (HVOF) process as an alternative to hard chrome plating. The question to be answered is if the performance of the alternative candidate is at least comparable to results obtained for hard chrome plating. The objective of this research is to compare the influence of the WC-10Co-4Cr coating applied by HVOF process and hard-chromium electroplating on the fatigue strength of AISI 4340 steel with and without shot peening. S-N curves were obtained in axial fatigue tests for the base material, chromium plated and tungsten carbide coated specimens. Copyright © 2001 Society of Automotive Engineers, Inc.